(untitled) (Research, Society and Development, 2020)
To estimate the prevalence of dental fear in schoolchildren and verify its association with gender, age group and oral health habits. Cross-sectional study with 44 elementary students from public schools. Data on sociodemographic issues and children’s oral health habits were collected and the Children’s Fear Survey Schedule - Dental Subscale (CFSS-DS) questionnaire was applied. Descriptive analysis of the data was performed, Fisher’s Exact and U Mann-Whitney tests (p <0.05). The prevalence of dental fear was 6.8% and the average of the total score of the CFSS-DS was 26.43 ± 7.20, median of 24.50, IQR25-75 21-33, minimum score of 16 and a maximum of 42. Most children had a low level of dental fear (95.5%). The levels of dental fear did not show statistically significant associations between sex (p = 0.162), age group (p = 0.181), having visited the dentist once in life (p = 0.201), complaints of tooth pain (p = 0.522) and complaints of tooth sensitivity (p = 0.181). The prevalence of dental fear was low and most children had a low level of dental fear. There was no association between dental fear and the variables sex, age, having visited the dentist at any time in life, complaints of pain and complaints of dental sensitivity.